If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -9x = 11 + 8x Solving 28 + -9x = 11 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 28 + -9x + -8x = 11 + 8x + -8x Combine like terms: -9x + -8x = -17x 28 + -17x = 11 + 8x + -8x Combine like terms: 8x + -8x = 0 28 + -17x = 11 + 0 28 + -17x = 11 Add '-28' to each side of the equation. 28 + -28 + -17x = 11 + -28 Combine like terms: 28 + -28 = 0 0 + -17x = 11 + -28 -17x = 11 + -28 Combine like terms: 11 + -28 = -17 -17x = -17 Divide each side by '-17'. x = 1 Simplifying x = 1
| 5x-(x-3)-1=18 | | 34-5x=20+9x | | x^3-4x^2+9=0 | | 3(2y-1)=-8(6+y) | | 82-(6x+6)=6(x+4)+x | | x^2+9x-32=0 | | 6x-x^3+5x^2=0 | | 20+8(9-11)=-12 | | 4x+14-7x=18-15x+12x-4 | | 3(a+b)=2a+c | | 20x^2+24x-96=0 | | -3x+7=11 | | x^2+16x+11= | | 4y-1+y+22=5y+30-3y | | 7d-1=3d+7 | | -15=5(1+4m)-2m | | 6-7x=7x-9x+11 | | 9r^2-16p^2=0 | | 5x+12=2x-10 | | 36-3x=6x+22 | | 10x+9/24=-7/24 | | 8+5x=4x+9 | | x^2=10-3(4-x) | | 4(2x-3)=4 | | 8x^2-4x-18=0 | | 3(7+x)=2x+21 | | 11x=26 | | 187=2.8t+0.5(-.0209625668)t^2 | | -2(10x+3)= | | 8x=3.5 | | (5x+2)+(x+3)= | | -8(2x+6)-(x+7)= |